The Formation and Decay of an Unstable State of a Suspension of Hydrophobic Nanoporous Particles under Rapid Compression - Vladimir Borman; Anton Belogorlov; Vladimir Tronin (Nanomaterials, 2021)
The study of non-wetting liquid transport in a nanoporous medium is stimulated by the possible use of this process to absorb or accumulate mechanical energy. The filling of nanopores of suspended particles with a non-wetting liquid under decay of the unstable state, when the pressure increase rate is much higher than the rate of volume change, is studied. Based on the new experimental data and a theoretical model of the interacting modes of the spontaneous filling and filling under rapid compression, a picture of the percolation transition and a mechanism of liquid transport under such conditions are proposed. It is shown that a new dynamic filling threshold <semantics>P0</semantics> is reached. It is shown that the filling of the porous medium is the result of the slow mode of impact compression when the fast mode of spontaneous filling is continuously adjusted to the slow mode on a small time scale. The theoretical model of the interacting modes is based on the solving of a system of kinetic equations for the distribution functions <semantics>f(n,t)</semantics> and <semantics>F(n,t)</semantics> clusters of filled pores under rapid compression, respectively. It is shown that filling at <semantics>P=const</semantics> corresponds to the non-dissipative transport of liquid on a time scale smaller than the characteristic filling time. The proposed model quantitatively describes the experimental data. So, the response of suspension to impact is characterized by the positive feedback.